2011
DOI: 10.1002/pds.2203
|View full text |Cite
|
Sign up to set email alerts
|

Validation of The Health Improvement Network (THIN) database for epidemiologic studies of chronic kidney disease

Abstract: Purpose Chronic kidney disease (CKD) is a prevalent and important outcome and covariate in pharmacoepidemiology. The Health Improvement Network (THIN) in the U.K. represents a unique resource for population-based studies of CKD. We compiled a valid list of Read codes to identify subjects with moderate to advanced CKD. Methods A cross-sectional validation study was performed to identify codes that best define CKD stages 3–5. All subjects with at least one non-zero measure of serum creatinine after 1-Jan-2002 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 20 publications
1
63
0
Order By: Relevance
“…We used a large, population-based dataset that has been extensively validated for health outcomes [12,13]. This dataset, THIN, is fundamentally different from an insurance claims database; it is an electronic medical record maintained for the purpose of providing care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used a large, population-based dataset that has been extensively validated for health outcomes [12,13]. This dataset, THIN, is fundamentally different from an insurance claims database; it is an electronic medical record maintained for the purpose of providing care.…”
Section: Discussionmentioning
confidence: 99%
“…For practitioners who use THIN, it represents the entire medical record, and THIN data has previously been validated for health outcomes research [12,13]. Because patients in the UK must register with a general practitioner to receive non-emergent medical care through the National Health Service, THIN broadly represents the population.…”
Section: Methodsmentioning
confidence: 99%
“…It may also reflect that those with CKD at younger ages are likely to have fewer comorbidites when admitted to hospital and therefore have this recognised when discharge coding is carried out. 31 Denburg et al 17 looked at the recording of biochemistry results at a general practice level compared to the recognition of CKD on general practice coding, which again found low sensitivity but excellent specificity and high PPV. It is unclear, however, how many of the biochemistry results had been entered into GP systems manually.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…Although this would be a useful additional source of data, it was not available to us, would require assessment in its own right, and has been explored at least at a GP biochemistry recording level before. 17 Our biochemistry definition of no-CKD was all-inclusive, including impaired eGFR (at least one eGFR <60ml/min/1.73m 2 but not sustained) and eGFR not measured. However, we performed sensitivity analyses, defining "no CKD" as those with normal eGFR only and found that this only improved PPV and worsened NPV.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation